Price of Political Uncertainty: Evidence from Ghanaian Treasury Bills - Osei-Assibey, Kwame (International Journal of Economics and Financial Issues, 2016)
Whilst democracy facilitates stabilization, political uncertainty around elections can be costly to economic growth, especially if investors believe it increases earning uncertainty and causes them to reduce their investments until after elections. The paper conjectures that new democracies (whose political environments are widely accepted to be characterized by political uncertainty problems) will even have investors demanding some compensation to buy assets which are generally considered risk-free. Data on the Ghanaian treasury bills (T-Bills) market empirically supports this: Rates increase around elections (compared to non-election period), suggest that political uncertainty is even priced in a risk-free asset such as T-Bills, thus creating electoral cycles. The paper proposes that new democracies should endeavor to strengthen financial institutions and frameworks that promote policy credibility to help mitigate the cost of political uncertainty. Keywords: Political Uncertainty; New Democracies; Elections and Public Debt Financing JEL Classifications: D72; H59; G11; H30